Programa de monitoreo y acompañamiento pedagógico del desempeño docente en educación primaria. I.E. N° 80542 “Jorge Basadre Grohman”, Mollepata - Ávila Sánchez, Edgar Anacleto (2019)
The work carried out on a Program of monitoring and pedagogical accompaniment of the teaching performance in primary education of the I.E. N ° 80542 "Jorge Basadre Grohman" Mollepata, 2017, its main problem: To what extent Monitoring Program and educational support influences the performance of teachers in primary education in the Educational Institution No. 80542 "Jorge Basadre Grohmann" of Mollepata, in the year 2017? and formulated objective: To determine the influence of the Monitoring Program and educational support in teacher performance in primary education in the Educational Institution No. 80542 "Jorge Basadre Grohmann" of Mollepata, in 2017. The methodology used corresponds to a pre experimental design. There was the participation of 6 teachers, a non-probabilistic sample to measure the variables, the questionnaire was used according to the teacher performance variable. It is found to improve teacher performance after applying the monitoring program and educational support in Primary Education in Educational Institution No. 80542 "Jorge Basadre Grohmann" of Mollepata, in 2017